The impact of perceived teacher support on Chinese junior high school students’ academic self-efficacy: The mediating roles of achievement goals and academic emotions - Ren, Xiaodan; Jing, Bin; Li, Hongxia; Wu, Changcheng (Frontiers in Psychology, 2022)
Teacher support is an important external factor that influences students’ self-efficacy, but the mechanisms of the action between the two are not yet fully explored. The purpose of this study was to investigate whether achievement goals and academic emotions could play a chain mediating role between perceived teacher support and self-efficacy. The study sample was made up of 1,074 Chinese junior high school students, and three structural equation models were constructed using data collected from on questionnaires. The findings suggest that achievement goals and academic emotions can mediate the relationship between perceived teacher support and self-efficacy. Further analysis revealed that achievement goals and academic emotions may play a chain mediating role between perceived teacher support and self-efficacy. These findings provide reference points for further refinement of the mechanism of the role of perceived teacher support on self-efficacy. They also serve to remind front-line teachers to focus on how to provide adequate teacher support to students in the context of online education, especially with regard to students’ academic emotions.